OPERATIONAL AND TACTICAL REQUIREMENTS FOR THE CONSTRUCTION AND OPERATION OF A TACTICAL-LEVEL GEOINFORMATION SYSTEM - Zhukova, E. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2022)
The article is devoted to defining the goals and features of ensuring public security and law and order as a type of public administration. The article establishes that the goal of public security and law and order is to strengthen and maintain a safe environment, a high level of legal culture of participants in public relations and reduce the risks of harm and danger to their rights and obligations, interests and needs. The level of development of the legal support of public security and law and order is characterized as insufficient. Arguments are given that the most important component of ensuring public safety and law and order (prevention of offenses) has not been reflected at the legal level. The author found that an indefinite wide range of persons were named as subjects of the prevention of administrative offenses, but the scope of competence of each of them and the minimum systemic nature of their activities are absent. Arguments are given that the main achievements in ensuring public security and law and order are: a) specifying the scope of responsibility of officials and officials in their professional activities, which contain elements of coercion; b) legalization of the participation of civil society in ensuring public security and law and order in the Law of Ukraine "On National Resistance"; c) reducing the formalization of elections to public councils under law enforcement and other state bodies. It is concluded that the main shortcomings of the administrative-legal regulation of ensuring public security and law and order are: a) the lack of a unified law enforcement policy, lack of coordination, leading to competition and rivalry between different law enforcement agencies; b) the lack of a well-thought-out personnel policy for recruiting positions in law enforcement agencies, isolated cases of nepotism, leading to the occupation of senior positions, giving access to state secrets, by citizens of the aggressor state, previously convicted etc.; c) the uneven remuneration of law enforcement personnel, in which the difference between the wages of the head and his subordinates creates conditions for significant social stratification, which creates an imbalance in the moral climate in the units; d) the lack of a valid nationwide concept of crime prevention, which leads to a discrepancy between the efforts of subjects of law enforcement.
Keywords: public administration, legal support, public order, public security, law and order, purpose